Obstetric outcomes in women with polycystic ovary syndrome and isolated polycystic ovaries undergoing in vitro fertilization: a retrospective cohort analysis. (29th May 2014) - Wan, Hei Lok Tiffany; Hui, Pui Wah; Li, Hang Wun Raymond; Ng, Ernest Hung Yu
Abstract: Objective : This retrospective cohort study evaluated the obstetric outcomes in women with polycystic ovary syndrome (PCOS) and isolated polycystic ovaries (PCO) undergoing in vitro fertilization (IVF) treatment. Methods : We studied 104 women with PCOS, 184 with PCO and 576 age-matched controls undergoing the first IVF treatment cycle between 2002 and 2009. Obstetric outcomes and complications including gestational diabetes (GDM), gestational hypertension (GHT), gestational proteinuric hypertension (PET), intrauterine growth restriction (IUGR), gestation at delivery, baby's Apgar scores and admission to the neonatal intensive care unit (NICU) were reviewed. Results : Among the 864 patients undergoing IVF treatment, there were 253 live births in total (25 live births in the PCOS group, 54 in the PCO group and 174 in the control group). The prevalence of obstetric complications (GDM, GHT, PET and IUGR) and the obstetric outcomes (gestation at delivery, birth weight, Apgar scores and NICU admissions) were comparable among the three groups. Adjustments for age and multiple pregnancies were made using multiple logistic regression and we found no statistically significant difference among the three groups. Conclusion : Patients with PCO ± PCOS do not have more adverse obstetric outcomes when compared with non-PCO patients undergoing IVF treatment.